Virtue as a Benchmark for Spirituality in Business - Cavanagh, Gerald F. (Journal of business ethics, 2002)
Business people often consider spirituality a means of increasing integrity, motivation and job satisfaction. Yet certain spiritualities are superficial and unstable. Religion gives depth and duration to a spirituality, but may also sew divisiveness. A spirituality's ability to develop good moral habits provides a positive test of the "appropriateness" of that spirituality for business. Many successful business executives demonstrate a spirituality that does develop good moral habits.